Feminine Subjects in Masculine Fiction - Miller, M. author. aut Link
X, 220 p.
Keywords: Between 1870 and 1910 male authors were actively engaged with imagining new possibilities for women, at the same time as the central female figure continued to function as a troubling and unreachable object of aesthetic desire. This book examines these inscrutable female characters who were the ground on which fiction reinvented itself as Art.